Adsorption isotherm of multicomponent solution of Cu(II) ions, crystal violet, and methylene blue on Silica-Magnetite Porphyridium sp. algae hybrid. Issue 1 (May 2020) - Permatasari, D; Buhani,; Rilyanti, M; Suharso,
Abstract: Algae-silica hybrid (HA-S) from Porphyridium sp. has been modified by coating particles of magnetite (Fe3 O4 ) via a sol-gel process using (TEOS) to produce silica-magnetite algae hybrid (HA-SM). The produced material HA-SM was applied as adsorbent for the multicomponent solution adsorption of Cu(II) ions, crystal violet (CV), and methylene blue (MB). Identification of functional groups was performed by infrared spectrometer (IR) indicating that in HA-SM there are an active organic groups derived from Porphyridium sp., while silanol and siloxane derived from silica matrix. In addition, the results of the analysis using Scanning Electron Microscopy with Energy Dispersive X-Ray (SEM-EDX) showed HA-SM has more heterogeneous surface morphology. The adsorption model of the multicomponent solutions of Cu(II) ions, CV, and MB by HA-S and HA-SM tend to follow the model of Freundlich adsorption isotherm.